Improving Hand Function of Severely Impaired Chronic Hemiparetic Stroke Individuals Using Task-Specific Training With the ReIn-Hand System: A Case Series - Camona, Carolina; Wilkins, Kevin B.; Drogos, Justin; Sullivan, Jane E.; Dewald, Julius P. A.; Yao, Jun (Frontiers in Neurology, 2018)
Purpose: In this study, we explored whether improved hand function is possible in post-stroke chronic hemiparetic individuals with severe upper limb motor impairments when they participate in device-aided task-specific practice. Subjects: Eight participants with chronic stroke (>1-year post, mean: 11.2 years) with severely impaired upper extremity movement (UE Fugl-Meyer (UEFMA) score 10-24) participated this study. Methods: Subjects were recruited to participate in a 20-session intervention (3 sessions/7 weeks). During each session, participants performed 20-30 trials of reaching, grasping, retrieving and releasing a jar with the assistance of a novel electromyography-driven functional electrical stimulation (EMG-FES) system. This EMG-FES system allows for Reliable and Intuitive use of the hand (called ReIn-Hand device) during multi-joint arm movements. Pre, post, and 3-month follow-up outcome assessments included UEFMA, Chedoke McMaster Stroke Assessment, Grip dynamometry, the Box and Blocks Test, Active and Passive goniometrics for wrist and metacarpophalangeal flexion and extension (II, V fingers), the Nottingham Stereognosis Assessment (NSA), and the Cutaneous Sensory Touch Threshold Assessment. Results: A non-parametric Friedman test of differences found significant changes in Box and Blocks test scores (χ^2=10.38, p< .05), passive and active range of motion (χ^2=11.31, p< .05 and χ^2=12.45, p<.01, respectively), and NSA scores (χ^2=6.42, p< .05) following a multi-session intervention using the ReIn-Hand device. Conclusions: These results suggest that using the ReIn-Hand device during reaching and grasping activities may contribute to improvements in gross motor function and sensation (stereognosis) in individuals with chronic severe UE motor impairment following stroke.